A CF4 based positron trap. (10th October 2016) - Marjanović, Srdjan; Banković, Ana; Cassidy, David; Cooper, Ben; Deller, Adam; Dujko, Saša; Petrović, Zoran Lj
Abstract: All buffer-gas positron traps in use today rely on N2 as the primary trapping gas due to its conveniently placed a 1 Π electronic excitation cross-section. The energy loss per excitation in this process is 8.5 eV, which is sufficient to capture positrons from low-energy moderated beams into a Penning-trap configuration of electric and magnetic fields. However, the energy range over which this cross-section is accessible overlaps with that for positronium (Ps) formation, resulting in inevitable losses and setting an intrinsic upper limit on the overall trapping efficiency of ∼25%. In this paper we present a numerical simulation of a device that uses CF4 as the primary trapping gas, exploiting vibrational excitation as the main inelastic capture process. The threshold for such excitations is far below that for Ps formation and hence, in principle, a CF4 trap can be highly efficient; our simulations indicate that it may be possible to achieve trapping efficiencies as high as 90%. We also report the results of an attempt to re-purpose an existing two-stage N2 -based buffer-gas positron trap. Operating the device using CF4 proved unsuccessful, which we attribute to back scattering and expansion of the positron beam following interactions with the CF4 gas, and an unfavourably broad longitudinal beam energy spread arising from the magnetic field differential between the source and trap regions. The observed performance was broadly consistent with subsequent simulations that included parameters specific to the test system, and we outline the modifications that would be required to realise efficient positron trapping with CF4 . However, additional losses appear to be present which require further investigation through both simulation and experiment.